Dissemination of UV-Based Dryer for Rice Milling Business of Citra Mandiri Farmer Group in Perapaakan Village, Sambas Regency: Diseminasi Alat Pengering UV Dryer Pada Usaha Penggilingan Padi Kelompok Tani Citra Mandiri Desa Perapakan Kabupaten Sambas - Ekawati; Rahmatullah Rizieq; Manurung, Sondang Sylvia; Sigit Sugiardi; Bancin, Hardi Dominikus (Yayasan Ahmar Cendekia Indonesia, 2023)
Rice production and rising demand necessitate rice milling. The Citra Mandiri farmer group's rice milling operation still relies on sun irradiation to dry grains in the field, making it less efficient and limiting rice sales to Sambas Regency. UV Dryer drying technology distribution and counseling, marketing management support through packaging, trademarks, and online media marketing. This action led to the construction of an 8m × 10m UV Dryer drier house, which allows partners to dry twice as much harvested grain from 750 kg – 1000 kg to 1500 kg – 2000 kg in one day instead of two. Mitra's Cap Gunung rice bag lets partners promote their rice to different locations through IG's social media channels without worrying about mixed rice. Abstrak Produksi beras dan meningkatnya permintaan mengharuskan penggilingan padi. Operasi penggilingan padi kelompok tani Citra Mandiri masih mengandalkan penyinaran sinar matahari untuk mengeringkan gabah di lapangan, sehingga kurang efisien dan membatasi penjualan beras ke Kabupaten Sambas. Distribusi dan konseling teknologi pengeringan Uv Dryer, dukungan manajemen pemasaran melalui pengemasan, merek dagang, dan pemasaran media online. Tindakan ini mengarah pada pembangunan rumah pengering Pengering UV 8m × 10m, yang memungkinkan mitra untuk mengeringkan biji-bijian yang dipanen dua kali lebih banyak dari 750 kg – 1000 kg menjadi 1500 kg – 2000 kg dalam satu hari, bukan dua. Kantong beras Cap Gunung Mitra memungkinkan mitra mempromosikan beras mereka ke lokasi yang berbeda melalui saluran media sosial IG tanpa khawatir tentang beras campuran.